PENGARUH PENAMBAHAN ENZIM PAPAIN DARI KULIT PEPAYA VARIETAS BERBEDA TERHADAP RENDEMEN DAN KUALITAS VCO - khasanah, ismi; Herdyastuti, Nuniek (Unesa Journal of Chemistry, 2024)
VCO is a modification of the process of making coconut oil so that a purer product is produced. VCO can be made using various methods such as fermentation, acidification and enzymatic using protease enzymes such as papain. This research aims to determine the effect of adding the papain enzyme from Bangkok and California papaya peel varieties on the yield and quality of VCO. The quality of VCO determined is water content using the gravimetric method, free fatty acid content and peroxide value using the titrimetric method. The quality of VCO with the addition of papain enzyme from Bangkok papaya skin which has an activity value of 3.66 U/mL obtained a yield of 63.50%, water content of 0.71%, free fatty acid content of 0.32%, peroxide value of 3.50 meq /kg, and the density is 0.91 g/cm3. Meanwhile, VCO with the addition of papain enzyme from California papaya skin which had an activity value of 5.04 U/mL obtained a yield of 67.80%, water content of 0.17%, free fatty acid content of 0.16%, peroxide value of 2.00 meq/kg, and the density is 0.82 g/cm3. Based on SNI 7381-2008 VCO with the addition of papain enzyme from California papaya skin, the quality meets quality standards.